Advancing urban sustainability assessment: a novel DEA-based framework for multidimensional analysis in Chinese cities - Liqi Hu; Aijun Li; Yunming Kuang; Tuzhi Lin (Humanities & Social Sciences Communications)
Abstract Many cities worldwide grapple with social challenges due to uneven socio-economic development, jeopardizing their long-term sustainability. To address these issues—especially in developing countries—this study introduces an extended sustainability framework that tackles both infrastructure disparities and the need for quality socio-economic progress. This comprehensive framework incorporates three dimensions—economy-environment, infrastructure construction, and social development—each characterized by distinct internal structures. To capture the complex interactions among these dimensions, we develop a novel methodological framework: the DEA-based Benefit of the Doubt (BoD) model. This model assesses the efficiency of the extended system across diverse structural configurations. Additionally, our framework integrates relative weight indexes, coupling-related indicators, and the BP-DEMATEL model. Through an empirical focus on Chinese cities, our findings reveal an upward trend in China’s overall sustainability efficiency, albeit with considerable variability among cities. Specifically, overall efficiency has surged by 38.61%, with the social development dimension’s efficiency escalating by 40.19%. Although continuous improvements are observed in coupling-related indicators, certain cities remain challenged in achieving synchronized growth across all dimensions. Notably, the economy-environment dimension emerges as a pivotal driving factor, while infrastructure construction and social development dimensions are identified as crucial for long-term urban sustainability. This study offers policy-relevant insights to help governments optimize urban sustainability strategies, ensuring more tailored, data-driven, and inclusive urban development.